2011
DOI: 10.1016/j.combustflame.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Autoignition of n-butanol at elevated pressure and low-to-intermediate temperature

Abstract: Autoignition experiments for n-butanol have been performed using a heated rapid compression machine at compressed pressures of 15 and 30 bar, in the compressed temperature range of 675-925 K, and for equivalence ratios of 0.5, 1.0, and 2.0. Over the conditions studied, the ignition delay decreases monotonically as temperature increases, and the autoignition response exhibits single-stage characteristics. A non-linear fit to the experimental data is performed and the reactivity, in terms of the inverse of ignit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 58 publications
5
105
0
2
Order By: Relevance
“…This approach to mixture preparation has been validated in several previous studies by withdrawing gas samples from the mixing tank and analyzing the contents by GC/MS [14], GC-FID [20], and GC-TCD [21]. The study of Weber et al [14] verified that the mole fraction of fuel was within 5 % of the expected mole fraction and the study of Das et al [21] verified that the mole fraction of water was within 2 % of the expected value.…”
Section: Typical Experimental Proceduresmentioning
confidence: 87%
See 1 more Smart Citation
“…This approach to mixture preparation has been validated in several previous studies by withdrawing gas samples from the mixing tank and analyzing the contents by GC/MS [14], GC-FID [20], and GC-TCD [21]. The study of Weber et al [14] verified that the mole fraction of fuel was within 5 % of the expected mole fraction and the study of Das et al [21] verified that the mole fraction of water was within 2 % of the expected value.…”
Section: Typical Experimental Proceduresmentioning
confidence: 87%
“…Such analyses have been conducted in the past, for example in the work of Weber et al [14] and Mittal and Sung [15]. Previous analyses generally assumed that the uncertainty of each parameter was normally distributed and independent (i.e.…”
Section: Methods Of Uncertainty Analysismentioning
confidence: 99%
“…In this approach, continuous stirring is needed to ensure a homogeneous mixture, for instance by using a magnetic stirrer [cf. 44,65,[70][71][72][73][74][75]. In addition, the possibility of fuel cracking/pyrolysis within the mixture preparation vessel over an extended time period needs to be avoided, and characterization experiments should be conducted to confirm the assumptions of minimal/negligible fuel loss, mixture homogeneity, and non-decomposition of fuel in the mixture preparation vessel, as carried out in [e.g., 65,73,74].…”
Section: Uncertainties and Issues For Rcm Experimentsmentioning
confidence: 99%
“…An error propagation analysis is needed to determine the contributions of 37 these factors to the uncertainty of the calculation of the compressed temperature. Weber et al [73] reported that the largest contributor to the total uncertainty in compressed temperature is the error in the initial pressure measurement, whereas the contributions from the measurements of the initial temperature and the compressed pressure are less significant. In addition, the uncertainty of T C is dependent on the actual value of the initial pressure, but not on the values of the other quantities [73].…”
Section: Uncertainties and Issues For Rcm Experimentsmentioning
confidence: 99%
“…The present work is justified because of the great amount of studies where the auto-ignition of different fuels at low temperatures is analyzed. In them, the ignition delay is obtained in environments poor in oxygen, and the dilution is done by adding N 2 , Ar or CO 2 indistinctly [32][33][34]. This way to control the percent of oxygen is very useful to obtain ignition delays at different temperatures and pressures, and with different combustion temperatures.…”
Section: Justification and Objectivementioning
confidence: 99%